2022
DOI: 10.1007/s12144-022-03739-y
|View full text |Cite
|
Sign up to set email alerts
|

The positive effects of combined breathing techniques and cold exposure on perceived stress: a randomised trial

Abstract: A pranayama-inspired breathing technique, cold exposure, and their combined application were assessed for their potential to reduce perceived stress in adults and compared to a control group. An experiment involving four groups was conducted, yielding separate cells for breathing technique-only and cold exposure-only, as well as a combined treatment and a control group. Eighty-six individuals participated in the study. Perceived stress is measured employing the 10-item version of the Perceived Stress Scale (PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The overall effect size (of all three interventionsthe WHM, WHbM, or cold exposure only) calculated was considered a medium effect, compared to the control group. While all intervention groups experienced this effect over time, the combined practice of HVB and cold exposure (i.e., cold shower) yielded the highest benefit (Kopplin and Rosenthal, 2022).…”
Section: Wim Hof Breathing Methods and Tummo Meditationmentioning
confidence: 94%
See 2 more Smart Citations
“…The overall effect size (of all three interventionsthe WHM, WHbM, or cold exposure only) calculated was considered a medium effect, compared to the control group. While all intervention groups experienced this effect over time, the combined practice of HVB and cold exposure (i.e., cold shower) yielded the highest benefit (Kopplin and Rosenthal, 2022).…”
Section: Wim Hof Breathing Methods and Tummo Meditationmentioning
confidence: 94%
“…In fact, the WHbM led to significantly attenuated and enhanced proinflammatory and anti-inflammatory cytokine levels, respectively, with the cold exposure significantly enhancing the immunomodulatory effects of the WHbM (Zwaag et al, 2022). One randomised trial related to WHbM and perceived subjective stress has been published (Kopplin and Rosenthal, 2022); the combined group (daily cold shower and the WHbMessentially the WHM) exhibited a medium-large positive effect on perceived stress compared to a wait-list control group. The findings suggest that an application of the WHbM is associated with a statistically significant decrease in perceived stress.…”
Section: Wim Hof Breathing Methods and Tummo Meditationmentioning
confidence: 99%
See 1 more Smart Citation
“…PsyDAO, a decentralised autonomous organisation supporting research at the intersection of psychedelics and mental health, provided funding for participant payments for a sample of 200, so this was the largest possible, and also allowed for potential attrition. The two RCTs focusing on HVBR and mental health had nal samples of N = 108 (four groups; HVBR condition, n = 33) 8 and N = 86 participants (4 groups; HVBR condition, n = 20) 7 . The former study was not adequately powered statistically to compare HVBR with the other two breathwork techniques (only the combined effects of three breathwork conditions to a meditation condition), and the latter stated actually requiring a sample size of 100, however it detected a medium-large signi cant effect size for the WHM.…”
Section: Methodsmentioning
confidence: 99%
“…Eight weeks of WHM training was associated with lower self-reported depression in comparison to an inactive control 6 but this was an observational, non-randomised study limiting conclusions that can be drawn. On the other hand, a recent randomised trial showed two weeks of either the WHM (combination of daily cold shower and HVBR separately), solely HVBR, or cold exposure only were connected to lower subjective stress versus an inactive comparator, with the combination having the greatest effect 7 . However, the statistical analysis used was not explicit about whether interaction effects were signi cant, instead only showing post-hoc differences between groups in post-intervention levels of stress.…”
Section: Introductionmentioning
confidence: 99%